The characteristics of captopril challenge test–positive patients using various criteria. (August 2019) - Kidoguchi, Satoshi; Sugano, Naoki; Hayashi-Ishikawa, Naomi; Morisawa, Norihiko; Tokudome, Goro; Yokoo, Takashi
Introduction: The captopril challenge test (CCT) is the major confirmatory test for primary aldosteronism (PA), and frequently carried out because of its convenience. However, it presents false-negative results with a certain probability, and as there are many criteria for CCT, it is not concluded yet which criteria to use. Materials and methods: A total of 71 PA patients were evaluated. We compared CCT-positive and CCT-negative patients in the following three criteria: plasma aldosterone/renin ratio (ARR) >200 after the CCT (criterion 1); plasma aldosterone concentration (PAC) >120 pg/ml after the CCT (criterion 2); and PAC suppression <30% of PAC before CCT (criterion 3). Results: The positive rate was 70.4%, 64.8% and 54.9% for criterion 1, criterion 2 and criterion 3, respectively. With criterion 1, the baseline plasma renin activity was lower, thus baseline ARR was higher in CCT-positive patients. With criterion 2, PAC was higher and estimated sodium intake and K were lower in CCT-positive patients. With criterion 3, K and PAC were lower in CCT-positive patients. Although it was not significant, in the patients with high sodium intake, the positive rate of criterion 1 was higher than that of the other criteria. Conclusions: ARR>200 is the valuable criterion for the diagnosis of PA.